The Role of Woman In Improving Society: The Role of Woman In Improving Society (Journal of the College of Education for Women, 2019)
Abstract:One of the most prominent historical stage feature that is well- knownnowadays in the world is democracy issue. This issue gives man the right toreflect his concept and notions . It,s the world of freedom , human right andliberation of women. This leads to the principle of equality between womenand men which is put in the top of liberty and Improvement lists .Improvement can be defined as a group of means and ways that isused to direct human work to improve their level of life economically andsocially .This study contains three sections, the first presents the social state ofwomen in pre-history period . And the second section presents the theory ofimprovement as an important social phenomena .The Third and last section presents the working women and her role inimproving society through her work and through her family.